Identification of white wines by using two oppositely charged Poly(p-phenyleneethynylene)s individually and in complex - Han, Jinsong; Bender, Markus; Seehafer, Kai; Bunz, Uwe H. F. (Angewandte Chemie. International edition, 2016)
We present a simple array composed of an anionic and a cationic poly(para-phenyleneethynylene) (PPE), together with an electrostatic complex between the two of them. The individual PPEs and the PPE complex were employed in the sensing of white wines at pH 13; the complex was also successfully employed as a sensor element at pH 3. The sensing mechanism is fluorescence quenching. Thirteen different wines were differentiated by this chemical tongue, which consists of four elements. The fluorescence quenching is not induced by the major components of the wines. Compounds such as acids, sugars, and alcohols alone do not quench the fluorescence, but rather the colored tannins and other polyphenols contained in wine are the main quenchers. However, the major constituents of wine significantly modulate the quenching of the PPEs by the tannins.